FASHION BRANDS IN THE DIGITAL REALM: A BLEND OF CREATIVITY AND INNOVATIVE TECHNOLOGIES - Тетяна Валеріївна , Ременєва (Art and Design, 2024)
To investigate the dynamics of unique innovative projects that blend the art of fashion and technological advancements in design workflows. Approach involved methods of literary and analytical, systematic and structural, comparative analysis, synthesis and generalization; methods of systematization of visual sources, as well as formal, stylistic, compositional and coloristic analysis. The role of branding and design elements in the innovative communication of technology and fashion is investigated. The evolution of digital fashion and the methodological concept of the new fashion direction are analyzed. It is revealed how designer brands integrate innovative technologies into historical and artistic experience to produce avant-garde fabrics, clothing, footwear, and accessories. An overview of the employment of modern advanced technologies in the work of creative designers of the new generation is presented. Scientific novelty consists in performing a systematic analysis of the results of the work of leading global brands in the practical implementation of new design trends in the form of: a blend of breakthrough biotechnologies and avant-garde design as an alternative perspective for new living design products; active use of advanced IT technologies through digital materials, 3D prints and 3D animation software, along with animatronic robotic systems. The above is gaining massive popularity in design practice when creating luxury fashion items. Practical relevance of the research lies in coverage of the current trend practices adopted by contemporary designers and brands who experiment not only with shapes and cuts, but also with advanced technologies. There is a strong emphasis on the ecological nature of digital fashion, which may reduce the negative impact of the fast-fashion business on the global environment.